Veiled in smoke [large type] - Green, Jocelyn (Green, Jocelyn. Windy City saga, 2020)
"In 1871, as Chicago's Great Fire destroys their bookshop, Meg and Sylvie Townsend make a harrowing escape with the help of reporter Nate Pierce. But when their father is committed to an asylum after being accused of murder, they must prove his innocence before the asylum truly drives him mad"--Provided by publisher.